Playful learning? An extreme comparison of the Children’s University in Malaysia and in Australia (Journal of Applied Learning and Teaching, 2019)
Playful learning is frequently conceived in binaries: fun/hard, child/adult, and formal/non-formal learning. The term ‘playful learning’ lacks a coherent definition. This is understandable given it is a multidisciplinary field of research. The article develops an extreme-comparative method to analyse a non-formal learning program, the Children’s University, in Malaysia and in Australia. It reveals structural differences in implementation, attitudes to playful learning, and cultural attitudes to non-formal learning. The cases draw on in-depth interviews with service providers. Finally, the article describes a ‘virtual circle’ which can be used to understand playful learning in different contexts.